Liquid ³He–⁴He mixture phase diagram in restricted geometry - Degtiarov, I.A.; Sokolov, S.S. (Физика низких температур, 2012)
The influence of van der Waals forces on the decay of liquid solutions of helium isotopes is studied theoretically
and the conditions for the phase co-existence in a confined geometry are investigated. As the models to account
the influence of van der Waals forces on the helium isotope solution the gap between two parallel planes
and the cylindrical channel are considered. For each of the models we calculated the concentration profile inside
the channel depending on the van der Waals constant, the initial solution concentration and the size of the channel.
The phase diagrams of liquid solutions are constructed. The obtained liquid mixture phase diagrams are
compared with the “bulk” phase diagram. A rather good agreement between theoretical and experimental phase
diagrams is obtained for liquid helium mixture in aerogel.